An Overview of 200 kW Solar Power Plant Based on Organic Rankine Cycle. (June 2016) - Zhang, Jianyuan; Zhao, Li; Wen, Jue; Deng, Shuai
Abstract: Solar-driven ORC-based distributed energy system (DES) is a potential integration energy solution for sustainable development of low carbon community. A 200 kW ORC DES system was demonstrated in Tianjin for a combined supply of power, heating, cooling and fresh water from solar thermal energy source. This paper briefly introduced the information about the design and construction of this demonstration project. The main components in 200 kW solar-driven multi-generation system are presented.